Investigating the impact of e-customer relationship management (eCRM) and digital innovation on the strategic competitive performance of small and medium-sized enterprises in Guilan province - Amin Ravan, Alireza (International Journal of Business Management and Entrepreneurship, 2022)
This research was conducted with the aim of investigating the impact of e-customer relationship management (eCRM) and digital innovation on the strategic competitive performance of small and medium-sized enterprises in Guilan province. The statistical population of the research included all employees of small and medium-sized enterprises in Guilan province, based on Morgan’s table, 384 questionnaires were distributed among the statistical population as a sample. The data collected by questionnaires was analysed by SPSS24 and AMOS24 software using structural equation modelling (SEM). The results of research showed that e-customer relationship management has a positive and significant effect on strategic competitive performance. Digital innovation has a positive and significant impact on strategic competitive performance. Finally, the results showed that digital innovation plays a mediating role in the relationship between eCRM and strategic competitive performance.